Analysis of Generation Z’s Reception of Javanese Cultural Content on the TikTok Account @kratonjogja.id - Rahmadanti, Novrian Dwiana; Azwar (International Journal of Science and Society, 2024)
This study explores how Generation Z perceives Javanese cultural content published through the TikTok account kratonjogja.id. The background of this research is the increasing role of social media, particularly TikTok, as a medium for promoting culture in the digital era. The method used is a qualitative reception analysis approach, focusing on the interpretation and experiences of audiences in consuming local cultural content. Data was collected through in-depth interviews with five informants representing this generation. The findings reveal three reception categories: dominant hegemonic position, negotiation, and opposition. Informants in the dominant hegemonic position fully accepted the content as engaging and relevant cultural education. Meanwhile, informants in the negotiation position appreciated the creativity of the content but felt that certain terms lacked adequate explanation. On the other hand, those in the opposition position found most cultural messages unclear and not aligned with their media preferences. The conclusion of this study is that TikTok can serve as a strategic platform for preserving local culture; however, improvements in content packaging are needed to make it more inclusive and informative for a heterogeneous audience. This study emphasizes the importance of collaboration between cultural traditions and technology to effectively reach younger generations.